Patient‐reported outcome of solifenacin treatment among women experiencing urinary urgency and urgency incontinence. Issue 1 (25th September 2013) - But, Igor; Orešković, Slavko; Bratuš, Dejan; Šprem‐Goldštajn, Marina; Hlebič, Gregor
Abstract: Objective: To evaluate treatment success and tolerability of solifenacin among women with urinary urgency (UU) and urgency urinary incontinence (UUI). Methods: In a prospective, observational, multicenter pilot study in Slovenia and Croatia, 100 women with UU and UUI were enrolled between January 2011 and July 2011. Patients received 5 mg of solifenacin once daily for 12 weeks and completed a 3‐day bladder diary, urgency questionnaire, Urogenital Distress Inventory (UDI), and Incontinence Impact Questionnaire (IIQ). Results: Overall, 91 women completed 12 weeks of treatment. Severity, frequency, and bother of UU significantly had decreased at weeks 4 and 12 ( P < 0.001). Improvement in UU led to an improvement in mean IIQ score: a reduction in UU frequency had the greatest impact ( P = 0.006). The mean treatment success rate was 74.2% (by visual analog score) and was closely related to the mean change in irritative UDI score ( r = 0.39; P < 0.001). Treatment success was greatest for patient perception of intensity of urgency scale (PPIUS; P = 0.003), UU bother ( P = 0.017), and micturition frequency ( P < 0.026). Dry mouth occurred in 35.2% of women at 4 weeks, and 27.7% at week 12. Conclusion: Solifenacin treatment was effective and well‐tolerated among women with UU and UUI. All overactive bladder symptoms had improved by week 12.